PENGARUH DESENTRALISASI FISKAL DAN PENDAPATAN ASLI DAERAH TERHADAP KINERJA KEUANGAN DAERAH KABUPATEN ACEH UTARA - Muhammad Ali; Maisyuri Maisyuri (LPPM STIE Lhokseumawe, 2017)
This study aims to Local Taxes and Levies significant effect on regional revenue in the city of Lhokseumawe. The population in this study is the City of Lhokseumawe. The sampling method in this study using total sampling, because the population examined in this study amounted to 1 by using the local budget realization report Lhokseumawe Municipal Government in 2008 - 2014. The equipment used in analyzing the data is multiple linear regression and hypothesis testing used for Test f and t-test. These results indicate that the coefficient R2 generated in this study was 32.5%. It shows that only 32.5% Local tax and retribusidapat variables explain the variable PAD. While the remaining 67.5% is explained by other studies.